Complimentary roles of religious institutions on the fight against examination malpractices in Nigeria (2009)
The campaign and the fight against examination malpractices have become the matters demanding a 'clarion call'. This study therefore investigated the roles that religious institutions play in the fight against examination malpractices in Nigeria. Three hundred respondents comprising students and adults from the Northern; Southern, and Eastern parts of on religious groups with which they associate. They also provided information on their religious leaders, how committed they are to religious activities and how aggressive they are on their fight against examination malpractices. The instrument used for data collection was Roles of Religious Institutions on the Fight Against Examination Malpractices Questionnaire (RRIFAEMQ). The Cronbach Alpha Reliability Coefficient estimated on RRIFAEMQ was 0.81. The data collected was analysed using descriptive statistics (frequency counts and cross tabulation). Compound bar charts were also used to present the results. It was found in the study that a good number of Nigerians are still not aggressive in their fight against examination malpractices. Greater percentage of Nigerians who received high quality moral instruction from their affiliated religious groups are very aggressive in their fight against examination malpractices. It was also found that greater percentage of Nigerians who are very close to their religious leaders and committed to religious activities are very aggressive in their fight against examination malpractices. Based on the findings of this study, it was recommended that, religious leaders should rise up to their responsibilities through sound moral teaching instead of running after monetary gains from members. Government should encourage moral instructions through religious institutions and media. 'Catch them young' approach should be employed too by integrating religious instructions into the school curriculum at all levels. There is a better future for Nigeria if special attention is paid to the above recommendation